KEKERASAN DALAM RUMAH TANGGA: DIMENSI HUKUM DAN KEADILAN BAGI PEREMPUAN DI INDONESIA - Ony Suryono; Ridwan Arifin (Badamai Law Journal, 2022)
Law and justice are one of the important issues in the development of law in Indonesia. Many studies show that there is a gap in the paradigm of justice that is obtained by the community. The community considers that justice in practice is heavily influenced by politics, even though the law should provide a sense of justice for the community, one of which is the victim in the crime of domestic violence (KDRT). The cases of domestic violence are increasing every year, and unfortunately women and children are the groups most vulnerable to becoming victims. This study aims to analyze the legal and justice aspects for women in cases of domestic violence. This study uses a normative juridical approach. This study finds and confirms that legal protection for women has been regulated in various legal instruments, ranging from the Law on the Elimination of Domestic Violence, the Law on Human Rights, and even the Law on the Protection of Witnesses and Victims.